A corrosion-resistant, high-plasticity, multi-component, low-expansion alloy and a preparation method thereof
By designing FeNiCoCr multi-component alloys and adopting appropriate heat treatment and plastic processing, the problems of insufficient strong plasticity and poor corrosion resistance at room temperature are solved, and a combination of high plasticity and excellent corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411079056.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Existing low-expanding alloys have insufficient strong plasticity at room temperature and have poor corrosion resistance, making it difficult to work stably in harsh environments for a long time.
The FeNiCoCr multi-component alloy is designed to obtain uniform and fine structure through appropriate heat treatment processes and plastic processing systems, ensuring that the alloy provides excellent strong plastic matching and corrosion resistance based on low expansion characteristics.
While maintaining low expansion performance, it significantly improves the corrosion resistance and strong plasticity of the alloy, solving the problem of impervious corrosion resistance of traditional low expansion alloys.
Smart Images

Figure CN119082625B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of metallic functional materials, and in particular relates to a corrosion-resistant, high-plasticity, multi-component, low-expansion alloy and a preparation method thereof. Background Art
[0002] Low expansion alloys (including Invar alloys, etc.) have low thermal expansion coefficients and high dimensional stability within a certain temperature range. 64 Ni 36 Invar alloy was first proposed in 1896 and has been widely used in precision machining, aerospace and other fields. However, the strength of traditional Invar alloy is not high, which limits its application as a load-bearing structural component, and it is difficult to process it into parts with complex shapes. Due to the poor corrosion resistance of traditional Invar alloy, it is also difficult to work stably for a long time in harsh environments. With the expansion of application fields and the increase in social needs, researchers have tried from two angles in recent years: optimizing the heat treatment and plastic processing system of traditional low-expansion Invar alloy, and alloying with rare earth elements or other elements. Although certain results have been achieved, it has caused the loss of low expansion performance and increased costs. More than one researcher expected to improve the overall corrosion resistance by adding Cr elements, but found that the alloy lost its low expansion characteristics. At present, there is a lack of breakthroughs in the development and research of low-expansion alloys, and finding suitable alloy design ideas and methods to achieve a comprehensive improvement in the low expansion performance and other properties of the alloy is still an important research topic in this field. Summary of the invention
[0003] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0004] In view of the above and / or existing problems in the prior art that low expansion materials have insufficient room temperature strength and plasticity and poor corrosion resistance, the present invention is proposed.
[0005] One of the purposes of the present invention is to provide a corrosion-resistant, high-plasticity, multi-component, low-expansion alloy, design a FeNiCoCr multi-component alloy, and use appropriate heat treatment processes and plastic processing systems to obtain a uniform and fine organizational structure, so as to provide excellent alloy strength and plasticity combination and corrosion resistance while ensuring low expansion characteristics.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a corrosion-resistant, high-plasticity, multi-component, low-expansion alloy, the structure of the alloy is a single face-centered cubic, and the alloy is composed of 51-57% Fe, 20-25% Ni, 15-21% Co, and 3-10% Cr in terms of mass percentage;
[0007] Among them, the sum of the mass percentages of Fe, Ni and Co is ≤97% and ≥90%; the sum of the mass percentages of Cr is ≥3% and ≤10%; and the sum of the mass percentages of each component is 100%.
[0008] As a preferred solution of the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, the alloy is composed of 51-56% Fe, 21-24% Ni, 16-18% Co, and 3-9% Cr in terms of mass percentage.
[0009] The present invention adopts a multi-component alloy design concept and uses high-purity Fe, Co, Ni, and Cr alloy raw materials to obtain a low expansion alloy with excellent corrosion resistance and high plasticity;
[0010] Fe is an important strengthening element that improves the strength and machinability of the alloy, and as a transition metal element itself, it can enhance the magnetism of the alloy. The addition of Co and Ni can produce strong ferromagnetic coupling with the Fe element, increase the Curie temperature and improve the low expansion performance, and both are infinitely solid-dissolved with the Fe element. Among them, the Co element can enhance the solid solution strengthening of the alloy; the Ni element can stabilize the face-centered cubic configuration of the alloy and improve the plasticity of the alloy. To ensure that the role of each element can be effectively exerted, the present invention requires that the mass percentages of the three elements of Fe, Co, and Ni are all greater than 10%. However, the raw material prices of the Co element and the Ni element are high. The present invention further designs that the mass percentage of the Fe element is 2 to 3 times that of the Co element and the Ni element, respectively.
[0011] Cr is an important anti-corrosion element. The Cr2O3 produced during the service of the alloy acts as a dense film to enhance the passivation of the alloy. However, the addition of Cr generally damages the low expansion characteristics of the alloy. For example, it was proposed in patents CN1099431A and CN1097812A that only less than 3wt.% of Cr can be added to the low expansion alloy for alloying, otherwise the average thermal expansion coefficient requirement cannot be met. This is because the addition of non-ferromagnetic elements may destroy the overall ferromagnetic configuration. However, in a multi-component single-phase alloy system, its thermodynamic properties and isotropic crystal structure may stabilize the magnetic configuration of the alloy and reduce the sensitivity of the alloy system. At the same time, the Cr element can be randomly arranged in the lattice and coupled with the surrounding elements. Under the combined effect, it does not necessarily destroy the magnetic configuration of the system. Therefore, when a specific content range of Cr is added to the multi-component system, the alloy may still maintain low expansion performance. And the stabilization effect of the Cr element on the face-centered cubic phase is also very critical. Different from previous research techniques, the specific Cr-containing component design confirmed by the present invention can obtain a low expansion alloy with significantly improved corrosion resistance.
[0012] As a preferred solution of the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, the alloy has the following characteristics:
[0013] (a) The thermal expansion coefficient is as low as 1.34×10 before 373K -6 ~5.05×10 -6 K -1 ;
[0014] (b) The saturation magnetization at room temperature is 0.6 to 1.6 T;
[0015] (c) coercive force of 85 to 140 A / m;
[0016] (d) The self-corrosion current in 3.5wt.% NaCl solution at room temperature is 5~8×10 -7 Amps.cm 2 ;
[0017] (e) The self-corrosion potential in 3.5wt.% NaCl solution at room temperature is -0.2 to -0.4V;
[0018] (f) The corrosion rate in 3.5wt.% NaCl solution at room temperature is 1.0-4.0mg.cm -2 .d -1 ;
[0019] (g) The tensile strain rate at room temperature is 10 -3 s -1 When the elongation after fracture is greater than 55%;
[0020] (h) The tensile yield strength at room temperature is 170-250 MPa, and the tensile strength is 430-470 MPa.
[0021] Another object of the present invention is to provide a method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy as described above, comprising:
[0022] The components are mixed according to the mass percentage of the alloy, smelted under inert gas protection or vacuum conditions, cast to obtain alloy ingots, and the ingots are heat treated to obtain the alloy.
[0023] As a preferred scheme for the preparation method of the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, wherein: the smelting is carried out under inert gas protection conditions, the furnace chamber is purged multiple times, and then the inert gas is filled and the gas pressure is maintained at 0.000001-0.05MPa.
[0024] As a preferred solution of the method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, the heat treatment includes hot rolling, homogenization, cold rolling and annealing.
[0025] As a preferred solution of the method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, the hot rolling temperature is 700-1200K, and the reduction is 20-60%.
[0026] As a preferred solution of the method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, wherein: the homogenization treatment has a temperature of 1073-1473K and a holding time of 1-6h.
[0027] As a preferred solution of the method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, the cold rolling reduction is 40 to 80%.
[0028] As a preferred solution of the method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy of the present invention, the annealing treatment is performed at a temperature of 673 to 1273 K and a holding time of 5 to 60 minutes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention obtains a corrosion-resistant, high-plasticity, multi-component low-expansion alloy with good strength and plasticity and greatly improved corrosion resistance, while maintaining the low expansion performance and improving other comprehensive properties of the Invar alloy, solving the problem of the current traditional low-expansion Invar alloy being not corrosion-resistant. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0032] Figure 1 This is the XRD spectrum of the alloy material of Example 1 of the present invention.
[0033] Figure 2 The scanning electron microscope morphology image and energy spectrum distribution image of the alloy material of Example 1 of the present invention are shown.
[0034] Figure 3 This is the EBSD scanning image of the alloy material of Example 1 of the present invention.
[0035] Figure 4 This is a diagram of the thermal expansion performance of the alloy material of Example 1 of the present invention.
[0036] Figure 5 This is the hysteresis loop diagram of the alloy material of Example 1 of the present invention.
[0037] Figure 6 This is a room temperature tensile engineering stress-strain curve of the alloy material of Example 1 of the present invention.
[0038] Figure 7 This is the XRD spectrum of the alloy material of Example 2 of the present invention.
[0039] Figure 8 The scanning electron microscope morphology image and energy spectrum distribution image of the alloy material of Example 2 of the present invention are shown.
[0040] Fig. 9 This is the EBSD scanning image of the alloy material of Example 2 of the present invention.
[0041] Fig.10 This is a diagram of the thermal expansion performance of the alloy material of Example 2 of the present invention.
[0042] Fig.11 This is the hysteresis loop diagram of the alloy material of Example 2 of the present invention.
[0043] Fig.12 This is a room temperature tensile engineering stress-strain curve of the alloy material of Example 2 of the present invention.
[0044] Fig.13 This is the XRD spectrum of the alloy material of Example 3 of the present invention.
[0045] Fig.14 The scanning electron microscope morphology image and energy spectrum distribution image of the alloy material of Example 3 of the present invention are shown.
[0046] Fig.15 This is the EBSD scanning image of the alloy material of Example 3 of the present invention.
[0047] Fig.16 This is a diagram of the thermal expansion performance of the alloy material of Example 3 of the present invention.
[0048] Fig.17 This is the hysteresis loop diagram of the alloy material of Example 3 of the present invention.
[0049] Fig.18 This is a room temperature tensile engineering stress-strain curve of the alloy material of Example 3 of the present invention.
[0050] Fig.19 This is the XRD spectrum of the alloy material of Comparative Example 1 of the present invention.
[0051] Fig. 20 The scanning electron microscope morphology image and energy spectrum line scanning image of the alloy material of comparative example 1 of the present invention are shown.
[0052] Fig.21 This is a macroscopic morphology diagram of the hot-rolled alloy material of comparative example 1 of the present invention.
[0053] Fig. 22 This is the XRD spectrum of the alloy material of Comparative Example 2 of the present invention.
[0054] Fig.23 This is a hot-rolled surface crack morphology of the alloy material of Comparative Example 2 of the present invention.
[0055] Fig.24 This is the XRD spectrum of the alloy material of Comparative Example 3 of the present invention.
[0056] Fig.25 This is the EBSD scanning image of the alloy material of comparative example 3 of the present invention.
[0057] Fig.26 This is the XRD spectrum of the alloy material of Comparative Example 4 of the present invention.
[0058] Fig. 27 This is the EBSD scanning image of the alloy material of comparative example 4 of the present invention.
[0059] Fig.28 This is a thermal expansion performance diagram of the alloy material of Comparative Example 4 of the present invention.
[0060] Fig.29 This is the hysteresis loop diagram of the alloy material of comparative example 4 of the present invention.
[0061] Fig.30 This is a room temperature tensile engineering stress-strain curve of the alloy material of comparative example 4 of the present invention.
[0062] Fig.31This is the XRD spectrum of the alloy material of Comparative Example 5 of the present invention.
[0063] Fig.32 This is the EBSD scanning image of the alloy material of comparative example 5 of the present invention.
[0064] Fig.33 This is a thermal expansion performance diagram of the alloy material of Comparative Example 5 of the present invention.
[0065] Fig.34 This is the hysteresis loop diagram of the alloy material of Comparative Example 5 of the present invention.
[0066] Fig.35 This is a room temperature tensile engineering stress-strain curve of the alloy material of comparative example 5 of the present invention. DETAILED DESCRIPTION
[0067] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0068] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0069] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0070] Unless otherwise specified, the raw materials used in the examples were purchased commercially.
[0071] Example 1
[0072] According to the chemical formula (Fe 57.5 Ni 24.5 Co 18 ) 96 Cr4 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3 After Pa, inert gas argon was filled in, and each alloy sample was turned over and melted repeatedly for 6 times to obtain a casting.
[0073] The obtained ingot was hot rolled at 1273K with a reduction of 50%. Then, it was subjected to a high temperature homogenization treatment at 1473K / 2h. Then, it was cold rolled with a reduction of 60%. Then, it was subjected to a recrystallization annealing treatment at 1223K / 10min. Before the heat treatment, the alloy samples were vacuum sealed (gas pressure ≤ 1Pa), and the heat treated samples were quenched, and finally, the alloy in Example 1 was obtained.
[0074] Depend on Figures 1 to 3 It can be seen that the obtained embodiment is a multi-component alloy containing Fe, Co, Ni, and Cr elements, with an FCC solid solution structure. The XRD results show that the alloy lattice constant is 0.3441nm, and all elements are evenly distributed. Statistics show that the grain size is 48.4±5μm. Figure 4 It shows that the sample has an extremely low thermal expansion coefficient at room temperature, and the thermal expansion coefficient is still as low as 1.34×10 at 373K. -6 K -1 From Table 1, it can be seen that the self-corrosion current and self-corrosion potential of the alloy are 6.19×10 -7 Amps / cm 2 and -0.355V, the corrosion rate is 2.34mg.cm -2 .d -1 . Figure 5 It shows that the saturation magnetization of the alloy is 1.14T and the coercive force is 132.7A / m at room temperature. Figure 6 It can be seen that the tensile yield strength of the alloy at room temperature reaches 249.9 MPa, the room temperature tensile strength reaches 464.4 MPa, and the tensile strain reaches 63.7%.
[0075] Example 2
[0076] According to the chemical formula (Fe 57.5 Ni 24.5 Co 18 ) 94 Cr6 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3 After Pa, inert gas argon was filled in, and each alloy sample was turned over and melted repeatedly for 6 times to obtain a casting.
[0077] The obtained ingot was subjected to a 50% reduction at 1273K. Then, it was subjected to a high temperature homogenization treatment at 1473K / 2h. After hot rolling, it was cold rolled with a reduction of 60%. Then, it was subjected to a recrystallization annealing treatment at 1223K / 10min. Before the heat treatment, the alloy samples were subjected to a vacuum sealing treatment (gas pressure ≤ 1Pa), and the heat-treated samples were subjected to a quenching treatment, and finally, the alloy in Example 2 was obtained.
[0078] Depend on Figures 7 to 9 It can be seen that the obtained embodiment is a multi-component alloy containing Fe, Co, Ni, and Cr elements, with an FCC solid solution structure. The XRD results show that the alloy lattice constant is 0.3436nm, and all elements are evenly distributed. Statistics show that the grain size is 47.4±5μm. Fig.10 It shows that the sample has an extremely low thermal expansion coefficient at room temperature, and the thermal expansion coefficient is still as low as 2.47×10 at 373K. -6 K -1 From Table 1, it can be seen that the self-corrosion current and self-corrosion potential of the alloy are 6.41×10 - 7 Amps / cm 2 and -0.343V, the corrosion rate is 1.66mg.cm -2 .d -1 . Fig.11 It shows that the saturation magnetization of the alloy is 0.88T and the coercive force is 101.4A / m at room temperature. Fig.12 It can be seen that the room temperature tensile yield strength of the alloy reaches 184.6 MPa, the room temperature tensile strength reaches 453.4 MPa, and the tensile strain reaches 59.7%.
[0079] Example 3
[0080] According to the chemical formula (Fe 57.5 Ni 24.5 Co 18 ) 92 Cr8 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3 After Pa, inert gas argon was filled in, and each alloy sample was turned over and melted repeatedly for 6 times to obtain a casting.
[0081] The obtained ingot was hot rolled at 1273K with a reduction of 50%. Then, it was subjected to a high temperature homogenization treatment at 1473K / 2h. Then, it was cold rolled with a reduction of 60%. Then, it was subjected to a recrystallization annealing treatment at 1223K / 10min. Before the heat treatment, the alloy samples were vacuum sealed (gas pressure ≤ 1Pa), and the heat treated samples were quenched, and finally, the alloy in Example 3 was obtained.
[0082] Depend on Figures 13-15 It can be seen that the obtained embodiment is a multi-component alloy containing Fe, Co, Ni, and Cr elements, with an FCC solid solution structure. The XRD results show that the alloy lattice constant is 0.3433nm, and all elements are evenly distributed. Statistics show that the grain size is 48.9±5μm. Fig.16It shows that the sample has a low thermal expansion coefficient at room temperature, and the thermal expansion coefficient is still as low as 5.05×10 -6 K -1 From Table 1, we can see that the self-corrosion current and self-corrosion potential of the alloy are 5.70×10 - 7 Amps / cm 2 and -0.349V, the corrosion rate is 1.46mg.cm -2 .d -1 . Fig.17 It shows that the saturation magnetization of the alloy is 0.59T and the coercive force is 86.9A / m at room temperature. Fig.18 It can be seen that the room temperature tensile yield strength of the alloy reaches 168.2 MPa, the room temperature tensile strength reaches 439.1 MPa, and the tensile strain reaches 60.9%.
[0083] Comparative Example 1
[0084] According to the chemical formula Fe 57.5 Ni 24.5 Co 18 (mass percentage) for batching, Fe, Ni, Co raw materials use their corresponding single substance particles (purity ≥ 99.95%). Wait until the pressure in the vacuum arc furnace is pumped to 5×10 -3 After Pa, inert gas argon was filled in, and each alloy sample was turned over and melted repeatedly for 6 times to obtain a casting.
[0085] The obtained ingot was hot rolled at 1273K with a reduction of 50%. Then, it was subjected to a high temperature homogenization treatment at 1473K / 2h. Then, it was cold rolled with a reduction of 60%. Then, it was subjected to a recrystallization annealing treatment at 1073K / 10min. Before the heat treatment, the alloy samples were vacuum sealed (gas pressure ≤ 1Pa), and the heat-treated samples were quenched. Finally, the alloy in Comparative Example 1 was obtained.
[0086] Depend on Figures 19-20 It can be seen that the alloy is mainly composed of quenched martensite. Fig.21 It shows that the samples do not exhibit low thermal expansion properties at room temperature to medium and high temperatures, and begin to austenitize at around 550°C. Fig. 22 It shows that the magnetization intensity of the alloy under an external field of 20000A / m at room temperature is 1.76T and the coercive force is 1703.0A / m. From Table 1, it can be seen that the self-corrosion current and self-corrosion potential of the alloy are 22.06×10 -7 Amps / cm 2 and -0.452V, the corrosion rate is 4.00mg.cm -2 .d -1 .Depend on Fig.23It can be seen that the room temperature tensile yield strength of the alloy reaches 637.8 MPa, the room temperature tensile strength reaches 851.9 MPa, and the elongation reaches 24.6%.
[0087] Comparative Example 2
[0088] According to the chemical formula (Fe 57.5 Ni 24.5 Co 18 ) 98 Cr2 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3 After Pa, inert gas argon was filled in, and each alloy sample was turned over and melted repeatedly for 6 times to obtain a casting.
[0089] The obtained ingot was hot rolled at 1273K with a reduction of 50%. Then, it was subjected to a high temperature homogenization treatment at 1473K / 2h. Then, it was cold rolled with a reduction of 60%. Then, it was subjected to a recrystallization annealing treatment at 1073K / 10min. Before the heat treatment, the alloy samples were vacuum sealed (gas pressure ≤ 1Pa), and the heat treated samples were quenched. Finally, the alloy in Comparative Example 2 was obtained.
[0090] Depend on Figures 24-25 It can be seen that the obtained comparative example multi-component alloy has a two-phase structure consisting of quenched martensite and retained austenite. Fig.26 It shows that the samples do not show low thermal expansion phenomenon at room temperature to medium and high temperatures, and begin to austenitize at around 500°C. Fig. 27 It shows that the magnetization intensity of the alloy under an external field of 20000A / m at room temperature is 1.61T and the coercive force is 829.1A / m. From Table 1, it can be seen that the self-corrosion current and self-corrosion potential of the alloy are 19.56×10 -7 Amps / cm 2 and -0.461V, the corrosion rate is 3.92mg.cm -2 .d -1 .Depend on Fig.28 It can be seen that the room temperature tensile yield strength of the alloy reaches 480.3 MPa, the room temperature tensile strength reaches 788.0 MPa, and the elongation reaches 29.5%.
[0091] The corrosion resistance of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 is shown in Table 1.
[0092] Table 1
[0093]
[0094] Comparative Example 3
[0095] According to the chemical formula (Fe57.5 Ni 24.5 Co 18 ) 96 Cr4 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3 After the temperature reaches 10000 Pa, inert gas argon is filled in, and each alloy sample is turned over and smelted repeatedly for 6 times to obtain a casting billet, which is the alloy in Comparative Example 3.
[0096] Depend on Fig.29 It can be seen that the obtained comparative example multi-component alloy is a face-centered cubic solid solution structure rich in Fe, Ni, Co, and Cr elements. Fig.30 It can be seen that there is a slight element segregation and a clear contrast difference in the structure. The matrix is rich in Ni and Cr elements, and the second phase is rich in Fe and Co elements. This is because the vacuum and furnace cleaning process was not strictly followed during the material smelting process, and impurities were introduced, causing segregation of the ingot. Fig.31 It can be seen that the differences in the internal composition and organization of the alloy make the material prone to stress concentration and cause the cast alloy to crack during hot rolling.
[0097] Comparative Example 4
[0098] According to the chemical formula (Fe 57.5 Ni 24.5 Co 18 ) 94 Cr6 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3 After the temperature reaches 10000 Pa, inert gas argon is filled in, and each alloy sample is turned over and smelted repeatedly for 6 times to obtain a casting billet, which is the alloy in Comparative Example 4.
[0099] Depend on Fig.32 It can be seen that the obtained multi-component alloy of this comparative example is a single face-centered cubic solid solution structure rich in Fe, Ni, Co, and Cr elements. Fig.33 It was shown that after the sample was kept at 1373K for more than 20 minutes, severe decarburization and grain boundary oxidation occurred on the surface, which led to surface cracking of the cast alloy during hot rolling.
[0100] Comparative Example 5
[0101] According to the chemical formula (Fe 57.5 Ni 24.5 Co 18 ) 92 Cr8 (mass percentage) is used for batching, and Fe, Ni, Co, and Cr raw materials use their corresponding single-substance particles (purity ≥ 99.95%). When the pressure in the vacuum arc furnace is pumped to 5×10 -3After Pa, inert gas argon was filled in, and each alloy sample was turned over and melted repeatedly for 6 times to obtain a casting.
[0102] The obtained ingot was hot rolled at 1273K with a reduction of 50%. Then, it was subjected to a high temperature homogenization treatment at 1473K / 2h. Then, it was cold rolled with a reduction of 60%. Then, it was subjected to a recrystallization annealing treatment at 1073K / 10min. Before the heat treatment, the alloy samples were vacuum sealed (gas pressure ≤ 1Pa), and the heat treated samples were quenched. Finally, the alloy in Comparative Example 5 was obtained.
[0103] Depend on Fig.34 It can be seen that the obtained multi-component alloy of this comparative example is a single face-centered cubic solid solution structure rich in Fe, Ni, Co, and Cr elements. Fig.35 It is shown that after the sample was recrystallized and annealed at 1073K for 20 minutes, the distortion energy distribution was inconsistent due to the uneven deformation of the structure, and after annealing at a relatively low temperature, a heterogeneous structure with extremely uneven grain size distribution was formed.
[0104] It can be seen from Examples 1, 2, 3 and Comparative Examples 1 and 2 that the change in Cr content significantly changes the low expansion performance, magnetic behavior and mechanical properties of the alloy. Too little Cr content will cause the alloy structure to undergo quenching martensitic phase transformation during cooling, and the FCC single-phase structure cannot be obtained. The high-density substructure and a large number of dislocations in the alloy reduce its plasticity and corrosion resistance, and also cause the alloy to not have a low expansion effect. With a moderate Cr content, this series of low expansion alloys can obtain a single face-centered cubic structure alloy after the final recrystallization annealing, and the grain size is stable, and the Fe, Ni, Co, and Cr elements are evenly distributed. It shows excellent low expansion characteristics and good corrosion resistance and mechanical properties. As the Cr content further increases, the alloy's saturation magnetization and coercivity decrease, the alloy's low expansion performance weakens, and the corrosion resistance is further improved. At the same time, the increase in Cr content leads to a decrease in the strengthening element Fe content, a weakened overall strengthening effect, and a decrease in yield strength and tensile strength at room temperature. And the elongation of all embodiments is greater than 55%, which shows that this alloy system has the characteristic of high plasticity.
[0105] Comparing Example 1 with Comparative Example 3, it can be seen that: irregular smelting operations, such as failure to clean the furnace in a standardized manner or the introduction of other impurities, will seriously affect the quality of the ingot, leading to component segregation and deterioration of the overall performance of the material. Comparative Example 4 selected a higher hot rolling temperature and holding time than Example 2, causing severe oxidation on the surface of the alloy and producing microcracks. During the rolling process, the surface oxides are embedded into the interior of the alloy, causing the cracks to form and expand. Comparing Example 3 with Comparative Example 5, it can be seen that: the unreasonable heat treatment system and the lower recrystallization temperature cause the areas with larger distortion to nucleate and grow rapidly, while the areas with smaller distortion energy nucleate more slowly and are difficult to grow, resulting in extremely uneven grain size distribution after alloy annealing and the production of a heterogeneous structure.
[0106] The present invention is guided by the multi-component alloy design concept to design a FeNiCoCr face-centered cubic single-phase alloy with uniform component distribution and non-equiatomic ratio. A fine and uniform grain size structure is obtained by combining a suitable heat treatment process and a plastic processing system. The thermal expansion coefficient of the alloy is as low as 1.34×10 -6 K -1 , and also exhibits soft magnetic properties, excellent corrosion resistance and strong plasticity. It can further promote the research, application and development of low expansion alloys with excellent comprehensive performance.
[0107] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A corrosion-resistant, high-plasticity, multi-component, low-expansion alloy, characterized in that: The structure of the alloy is a single face-centered cubic structure, and the alloy is composed of 51-56% Fe, 21-24% Ni, 16-18% Co, and 3-9% Cr in terms of mass percentage; Among them, the sum of the mass percentages of Fe, Ni and Co is ≤97% and ≥90%; the sum of the mass percentages of each component is 100%; The components are mixed according to the mass percentage of the alloy, smelted under inert gas protection or vacuum conditions, cast to obtain alloy ingots, and the ingots are heat treated to obtain the alloy; the heat treatment includes hot rolling, homogenization, cold rolling and annealing in sequence; The hot rolling temperature is 700-1200 K, and the reduction is 20-60%; The homogenization treatment is performed at a temperature of 1073-1473 K and a holding time of 1-6 h; The cold rolling reduction is 40-80%; The annealing treatment is performed at a temperature of 673-1273 K and a holding time of 5-60 minutes; The thermal expansion coefficient of the alloy is as low as 1.34×10 -6 ~5.05×10 -6 K -1 .
2. The corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 1, characterized in that: The alloy also has the following properties: (a) The saturation magnetization at room temperature is 0.6~1.6 T; (b) Coercive force is 85~140 A / m; (c) The self-corrosion current in 3.5 wt.% NaCl solution at room temperature is 5~8×10 -7 Amps / cm 2 ; (d) The self-corrosion potential in 3.5 wt.% NaCl solution at room temperature is -0.2~-0.4 V; (e) The corrosion rate in 3.5 wt.% NaCl solution at room temperature is 1.0~4.0 mg.cm -2 .d -1 ; (f) The tensile strain rate at room temperature is 10 -3 s -1 When the elongation after fracture is greater than 55%; (g) The tensile yield strength at room temperature is 170~250 MPa, and the tensile strength is 430~470 MPa.
3. The method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 1, characterized in that: include, The components are mixed according to the mass percentage of the alloy, smelted under inert gas protection or vacuum conditions, cast to obtain alloy ingots, and the ingots are heat treated to obtain the alloy.
4. The method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 3, characterized in that: The heat treatment includes hot rolling, homogenization, cold rolling and annealing in sequence.
5. The method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 4, characterized in that: The hot rolling temperature is 700-1200 K, and the reduction is 20-60%.
6. The method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 4, characterized in that: The homogenization treatment is performed at a temperature of 1073-1473 K and a holding time of 1-6 h.
7. The method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 4, characterized in that: The cold rolling reduction is 40-80%.
8. The method for preparing the corrosion-resistant, high-plasticity, multi-component, low-expansion alloy according to claim 4, characterized in that: The annealing treatment is performed at a temperature of 673-1273 K and a holding time of 5-60 minutes.
Citation Information
Patent Citations
An alloy sheet having high etching performance
CN1097812A
Alloy sheet and method for manufacturing thereof
CN1099431A
Low thermal expansion alloy
JP2024043238A